Islamic stock market determinants in Malaysia / Nur Amalin Sofia Abd Malek - Abd Malek, Nur Amalin Sofia (Faculty of Business and Management, 2018)
This study generally aim to see the dynamic impact between country stock return, changes in oil price and changes in gold price toward the Islamic stock return in Malaysia. This study used time series data analysis and Multiple Linear Regression Model in order to know the significant relationship between the dependent variable and independent variable. The data was obtained from Bursa Malaysia, Yahoo. Finance, Investing Website and Inveslopedia website that covering monthly data for 10 years period. The data collected from January 2008 until December 2017. Thus. the sample size of this study become 120 observation. This study use three different independent variable in order to know the impact toward Islamic stock return. This independent variable are country stock return. changes in oil prices and changes in gold prices. The result of this study found that, there is significant and positive relationship between country stock return toward Islamic stock market, while oil price and gold price are insignificant toward Islamic stock market.